Short Communication: The herpetofauna around human settlements in Lubuklinggau City, South Sumatra, Indonesia: Composition and diversity - Dian Samitra; Zico Fakhrur Rozi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Samitra D, Rozi ZF. 2020. The herpetofauna around human settlements in Lubuklinggau City, South Sumatra, Indonesia: Composition and diversity. Biodiversitas 21: 1432-1437. Herpetofauna research has been conducted mostly in conservation forest areas, so little is known about herpetofauna outside the conservation areas, such as those around the human settlements. The data of herpetofauna near human settlements are important in carrying out conservation actions. This study aimed to determine the diversity of herpetofauna around human settlements in the city of Lubuklinggau. The study was conducted from February to August 2019. Herpetofauna samples were taken in three habitats around settlements, i.e., plantation, rice field, and river. Sampling was done with the method of visual encounter survey and time-constrained search. The data were analyzed using ecological indexes, i.e., relative abundance, and indexes of diversity, evenness, similarity, and dominance. The results showed that 378 individuals of herpetofauna were found, belonging to 27 species (12 amphibians and 15 reptiles). Eighteen species were found in the plantation (7 amphibians and 11 reptiles), 15 species in the river (10 amphibians and 5 reptiles), and 14 species in the rice field (6 amphibians and 8 reptiles). Similarity index analysis showed that the rice field had quite different species from other habitats. The herpetofauna diversity around settlements was categorized as medium.